The Effect of Investor's Risk Appetite on the Stock Market: A Study on the BIST Financial Index - Nur, Tuğba (Ahmet Arif EREN, 2022)
In the study, it was aimed to investigate the relationship between Risk Appetite index (RISE) and BIST Financial index between 06.06.2008-07.11.2021 with linear ARDL, nonlinear ARDL, Toda & Yamamoto Granger causality, and Hatemi-J (2012) asymmetric causality tests. As a result of the analysis, it has been determined that there is a long-term cointegration relationship between BIST Financial and RISE indices according to linear ARDL and nonlinear ARDL models. According to the linear ARDL model long-term coefficient, it was determined that the 1% increase in the RISE index caused an approximately 44% increase in the BIST Financial index. According to the non-linear ARDL model results, it is observed that a 1% increase in positive changes in the RISE index causes an approximately 46% increase in the BIST Financial index, and a 1% increase in negative changes causes an approximately 43% increase in the BIST Financial index. Therefore, it can be said that there is a long-term asymmetric cointegration relationship between the indices. In addition to the findings, according to the results of the Toda & Yamamoto Granger causality tests, a one-way causality relationship was determined from BIST Financial index to the RISE index. According to Hatemi-J (2012) asymmetric causality test results, from the negative shocks in the RISE index to the negative shocks in the BIST Financial index, from the negative shocks in the RISE index to the positive shocks in the BIST Financial index, from the positive shocks in the BIST Financial index to the positive shocks in the RISE index, and from the negative shocks in the BIST Financial index to the negative shocks in the RISE index causality relationship has been determined.

Çalışmada 06.06.2008-07.11.2021 döneminde Risk İştahı Endeksi (RISE) ve BIST Mali endeksi arasındaki ilişkinin doğrusal ARDL, doğrusal olmayan ARDL, Toda & Yamamoto Granger nedensellik ve Hatemi-J (2012) asimetrik nedensellik testleri ile araştırılması amaçlanmıştır. Doğrusal ARDL ve doğrusal olmayan ARDL modellerinden elde edilen bulgulara göre BIST Mali ve RISE endeksleri arasında uzun dönemli eşbütünleşme ilişkisinin olduğu tespit edilmiştir. Doğrusal ARDL model uzun dönem katsayısına göre RISE endeksinde meydana gelen %1’lik artışın BIST Mali endeksinde yaklaşık %44’lük bir artışa sebep olduğu, doğrusal olmayan ARDL model sonuçlarına göre ise RISE endeksinde pozitif değişimlerde meydana gelen %1’lik artışın BIST Mali endeksinde yaklaşık %46’lık bir artışa, negatif değişimlerde meydana gelen %1’lik artışın BIST Mali endeksinde yaklaşık %43 artışa sebep olduğu gözlemlenmektedir. Dolayısıyla endeksler arasında uzun dönemli asimetrik bir eşbütünleşme ilişkisinin olduğu söylenebilmektedir. Bulgulara ek olarak Toda & Yamamoto Granger nedensellik testleri sonuçlarına göre BIST Mali endeksinden RISE endeksine doğru tek yönlü nedensellik ilişkisi, Hatemi-J (2012) asimetrik nedensellik test sonuçları göre ise RISE endeksindeki negatif şoklardan, BIST Mali endeksindeki negatif şoklara, RISE endeksindeki negatif şoklardan, BIST Mali endeksindeki pozitif şoklara, BIST Mali endeksindeki pozitif şoklardan RISE endeksindeki pozitif şoklara, BIST Mali endeksindeki negatif şoklardan RISE endeksindeki negatif şoklara doğru asimetrik nedensellik ilişkisi tespit edilmiştir.
Yatırımcı Risk İştahının Pay Piyasasına Etkisi: BİST Mali Endeksi Üzerine Bir Araştırma
Keywords: Business Administration; İşletme